Long‐term feeding of hydroalcoholic extract powder of Lepidium meyenii (maca) enhances the steroidogenic ability of Leydig cells to alleviate its decline with ageing in male rats. (10th March 2017) - Yoshida, K.; Ohta, Y.; Kawate, N.; Takahashi, M.; Inaba, T.; Hatoya, S.; Morii, H.; Takahashi, K.; Ito, M.; Tamada, H.
Summary: This study examined whether feeding hydroalcoholic extract of Lepidium meyenii (maca) to 8‐week‐old (sexually maturing) or 18‐week‐old (mature) male rats for more than a half year affects serum testosterone concentration and testosterone production by Leydig cells cultured with hCG, 22R‐hydroxycholesterol or pregnenolone. Testosterone concentration was determined in the serum samples obtained before and 6, 12, 18 and 24 weeks after the feeding, and it was significantly increased only at the 6 weeks in the group fed with the maca extract to maturing rats when it was compared with controls. Testosterone production by Leydig cells significantly increased when cultured with hCG by feeding the maca extract to maturing rats for 27 weeks (35 weeks of age) and when cultured with 22R‐hydroxycholesterol by feeding it to mature rats for 30 weeks (48 weeks of age). Overall testosterone production by cultured Leydig cells decreased to about a half from 35 to 48 weeks of age. These results suggest that feeding the maca extract for a long time to male rats may enhance the steroidogenic ability of Leydig cells to alleviate its decline with ageing, whereas it may cause only a transient increase in blood testosterone concentration in sexually maturing male rats.